The Understanding Level of Students toward the Various Values of Character Education in Civics Courses of Elementary School - Rossy Arlinda; Pratiwi Pujiastuti; Wuri Wuryandani (STAI Hubbulwathan Duri, 2022)
The objective of this study is to know the understanding level of the various values of character education in Civics courses in Elementary School (PPKN SD) toward the students of Elementary School Teacher Education (ESTE), Education Faculty, at a state university in Yogyakarta. This is a descriptive quantitative study with a survey method. The population of this research are 307 ESTE students in the 2019 academic year. The samples were taken using random sampling, including 174 students. The instrument used was a multiple-choice test through a google form link. The instrument was validated by expert judgement. The data analysis technique used was descriptive analysis in a percentage. The result of the study shows that the understanding level of various values in character education in Civics courses of the elementary school toward ESTE students were categorized as